ERRATUM - de Editoração, Núcleo (Revista de Nutrição, 2023)
In article “Potential drug-food interactions in patients hospitalized in the Cardiology Unit” with DOI: 10.1590/1678-9865201932e180147, published in Revista de Nutrição, 2019;32:e180147, on page 1: